Differences of Retinal Nerve Fiber Layer and Ganglion Cell Layer-Inner Plexiform Layer Thickness in Patients without Diabetes Mellitus, with Diabetes Mellitus Type 2 without Diabetic Retinopathy and with Diabetic Retinopathy - Sukmawati, Nurindah; Suryathi, Ni Made Ari; Andayani, Ari; Pantjawati, Ni Luh Diah; Widiana, I Gde Raka; Yuliawati, Putu; Juliari, IGAM (Indonesian Vitreoretinal Society, 2025)
Introduction : Prevention of Diabetic Retinopathy (DR) require an examination method that can identify earliest damage before clinical symptoms observed. This study aimed to determine the novel and objective way to detect those damage through RNFL and GCL-IPL thickness. Method : This analytical cross sectional study research conducted at the eye polyclinic and the Diabetic Center of IGNG Ngoerah Hospital, Denpasar. This study comparing the difference in thickness of RNFL and GCL-IPL in patients without DM, with Type 2 DM without DR and with DR in average and each quadrant thickness through Kruskal Wallis and One Way Anova test. Result : The sample was 59 people which then divided into three groups, namely 20 samples in the group without DM, 19 samples in the DM group without DR and 20 samples with DR. The samples were then examined for RNFL and GCL-IPL and the results were compared between groups. The mean age of the subjects were 58.80±9.65 years old. In the RNFL measurement, it was found that there were differences in values ​​between groups in all quadrants except the temporal quadrant (p=0.518). After covariate analysis by variables of age, HbA1c, blood pressure, visual acuity, IOP and axial length, the results change with the nasal and inferior quadrants as the only found significant. In the GCL-IPL analysis there were significant differences between groups, especially in the superotemporal, temporal and inferotemporal quadrants (p<0.005). These results remained after being controlled by covariate analysis. Conclusion : This study proved a neurodegeneration process that occured focally in certain areas that can be detected through the RNFL and GCL-IPL measurement modalities. These examinations were expected to be useful in terms of screening both primary and secondary in patients with type 2 DM.